Impak program pembangunan Sarawak Land Consolidation and Rehabilitation Authority (SALCRA) ke atas kualiti hidup peserta projek pembangunan tanah hak adat bumiputera (NCR) di Betong, Sarawak - Incham, Anak Manggat (2025)
The Sarawak Land Consolidation and Rehabilitation Authority (SALCRA) is a program developed by the Malaysian government aimed at improving the quality of life of the Bumiputera community in rural area. The main aim of this study is to identify the quality of life and the impact of SALCRA development programme towards Native Customary Rights (NCR) landowners. The seven components of quality of life to explored in this study namely economics, housing, infrastructure, education, social, health and environmental. In addition, the perception towards SALCRA both generally and specifically are also identified in this study. A total of 300 SALCRA participants from Betong division were selected as respondents. The methodology of this study is mix method it is combination of quantitative and qualitative study. Chi-Square correlation analysis were performed to analyze the categorical data form meanwhile as for the continuous data independent student t-test was performed. The results indicated that the impacts of the SALCRA development programme positively impacted the quality of life of SALCRA participants whereabout stated scores above the 75 percents as a passing mark. The analysis of this study confirmed that several components of quality of life that yielded high mean scores were housing (92%), infrastructure (89.0%), education (88.0%), social (96.0%) and environmental (88.0%). Futhermore, perception towards SALCRA in general (77.0%) and specific (75.0%) also stated a good level of perception. SALCRA play an important roles in enhancing and improving the quality of life of the SALCRA participants in rural area of Sarawak.